Severity of pain and circadian changes in uterine artery blood flow in primary dysmenorrhea - Celik, Husnu; Gurates, Bilgin; Parmaksiz, Cem; Polat, Aytac; Hanay, Fethi; Kavak, Burcin; Artas, Zeynep Dogan (Springer Heidelberg, 2009)
To investigate the severity of pain and circadian changes in uterine artery blood flow in primary dysmenorrhea cases. The study included 27 cases diagnosed as primary dysmenorrhea and 25 individuals who had no dysmenorrhea complaint. Bilateral uterine artery systole/diastole rates (S/D), pulsatility indices (PI) and resistance indices (RI) of all cases were measured using transvaginal colour Doppler at 12.00-02.00 p.m. and 12.00-02.00 a.m. Severity of pain was evaluated in dysmenorrhea cases at the same hours using a verbal pain assessment scale. Doppler measurements of dysmenorrhea cases conducted at 12.00-02.00 p.m. showed right uterine artery S/D: 3.37 +/- A 0.26, RI: 0.73 +/- A 0.07, PI: 2.38 +/- A 0.34 and left uterine artery S/D: 3.33 +/- A 0.37, RI: 0.74 +/- A 0.14, PI: 2.41 +/- A 0.15, while measurements carried out at 12.00-02.00 a.m. showed right uterine artery S/D: 3.88 +/- A 0.12, RI: 0.87 +/- A 0.14, PI: 2.94 +/- A 0.21 and left uterine artery S/D: 3.90 +/- A 0.27, RI: 0.92 +/- A 0.12, PI: 2.93 +/- A 0.21. Comparisons revealed significantly higher Doppler indices at night (P < 0.05) than in the day in dysmenorrhea cases. There was not any significant circadian difference in individuals who did not have dysmenorrhea (P > 0.05). Pain score in the verbal pain assessment of dysmenorrhea cases was found 3.6 +/- A 1.4 in the day and 5.8 +/- A 1.7 at night. The difference was found significant (P < 0.05). Uterine artery blood flow is reduced at night in dysmenorrhea cases. In correlation with this, the cases feel more pain at night. Our results may be important on the planning of working hours and their quality of life.
Keywords: Uterin artery; Circadian rhythm; Primary dysmenorrhea